2022
DOI: 10.1007/s00415-022-11342-1
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2A receptor availability in patients with early- and moderate-stage Parkinson’s disease

Abstract: Introduction Adenosine 2A (A2A) receptors co-localize with dopamine D2 receptors in striatopallidal medium spiny neurons of the indirect pathway. A2A receptor activation in the striatum or pallidum decreases D2 signaling. In contrast, A2A receptor antagonism may help potentiate it. Furthermore, previous PET studies have shown increased A2A receptor availability in striatum of late-stage PD patients with dyskinesia. However, human in vivo evidence for striatal A2A receptor availability in early-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…It was supported by another study of 4026 patients by Hattori et al As reported the slower levodopa dose escalation was present in patients who were initially treated with istradefylline, especially when combined with ≥600 mg/day of L-DOPA, supporting that A2AR antagonists may slow the progressive LDD increases [38]. Recent studies conducted by Waggan et al (2022) revealed decreased availability of A2A receptor in the bilateral caudate nucleus in Parkinsonian patients with early stage of the disease in comparison with healthy controls (P = 0.02) [48]. Moderate-stage PD patients, on the other hand, showed its increased availability in the pallidum compared to healthy controls (P=0.03).…”
Section: The Effect Of A2ar Antagonism On Motor Symptoms Of Parkinson...mentioning
confidence: 94%
See 1 more Smart Citation
“…It was supported by another study of 4026 patients by Hattori et al As reported the slower levodopa dose escalation was present in patients who were initially treated with istradefylline, especially when combined with ≥600 mg/day of L-DOPA, supporting that A2AR antagonists may slow the progressive LDD increases [38]. Recent studies conducted by Waggan et al (2022) revealed decreased availability of A2A receptor in the bilateral caudate nucleus in Parkinsonian patients with early stage of the disease in comparison with healthy controls (P = 0.02) [48]. Moderate-stage PD patients, on the other hand, showed its increased availability in the pallidum compared to healthy controls (P=0.03).…”
Section: The Effect Of A2ar Antagonism On Motor Symptoms Of Parkinson...mentioning
confidence: 94%
“…Moderate-stage PD patients, on the other hand, showed its increased availability in the pallidum compared to healthy controls (P=0.03). Moreover, increased mean of striatal A2AR availability correlated with greater severity of motor symptom severity (P = 0.02) [48]. KW-6356, a novel A2AR antagonist and inverse agonist when administered to MPTP-treated marmosets significantly reversed motor impairments [87].…”
Section: The Effect Of A2ar Antagonism On Motor Symptoms Of Parkinson...mentioning
confidence: 95%
“…A2A receptors are highly expressed on neuronal surfaces in the striatum [54]. Several studies have used PET radiotracers targeting these receptors in animal models [55] and humans [56][57][58][59][60]. Even though studies have pointed toward the involvement of adenosine signaling in neuroinflammation, conclusive evidence in humans is scarce as the main use of A2A receptor-targeted radiotracers has been within the scope of their colocalization to D2 receptors [52].…”
Section: Propagating Neuroinflammation: the Role Of Adenosine Recepto...mentioning
confidence: 99%